Dualitas Hukum Atas Pengenaan Sanksi Kebijakan Pengampunan Pajak di Indonesia - Agus Suharsono (Jurnal Transformasi Administrasi, 2019)
Legal dualism over the imposition of sanction against tax amnesty policy arises due to the decision of provision formula regarding the sanction of 200% increase governed in Article 18 clause (3) of Tax Amnesty Law with collecting medium in the form of receivable tax stipulation document governed in Article 13 of General Provisions and Tax Procedures Law. The research method used is normative juridical approach to legislation, conceptual approach, and analytical approach. Research data in the form of primary and secondary legal sources obtained by literature study, analyzed qualitatively and presented descriptively. This dualism can be dealt with by including the provision of sanction in the amendment to the General Provisions and Tax Procedures Law becoming the prioritized national legislative program in 2019.